La multifonctionnalité de l'agriculture en pratique : étude des relations entre exploitations agricoles et étangs de la Dombes. - Christophe Toussaint Soulard (Cybergeo)
Multifunctionality of agriculture is nowadays recognized by rural and agricultural policies but we don’t know exactly what are its consequences on farm management and on farmer practices. A survey of some farms of a French rural area (la Dombes near Lyon) enabled the analysis of how farmers manage cultivated lands and fish production in ponds, hunting, and protection of birds. We identify areas, practices and farming organisation patterns which farmers take into account on their farms which affect the multifonctionnality of the territory. Our work opens a new way for an applicated research to help farmers to plan the use of land on their farm for sustainable development.